Mg-ZIF nanozymes disrupt the level of ROS for osteosarcoma killing via POD activity - Zheng, Junjie; Zhuo, Shiqiang; Huang, Lin; Wang, Jinying; Huang, Gaofeng (Frontiers in Pharmacology, 2024)
Osteosarcoma (OS) is notorious for its high malignancy, and conventional chemotherapy drugs, while killing tumor cells, often inflict significant harm on the patient's body.The tumor microenvironment of OS is characterized by high levels of hydrogen peroxide (H2O2).Leveraging this feature, we have developed Mg-ZIF nanoparticles, which incorporate magnesium (Mg) to confer robust peroxidase (POD)-like enzymatic activity. These Mg-ZIF nanozymes can generate highly lethal superoxide anions within tumor cells in a responsive manner, thereby achieving effective tumor destruction. Both in vitro and in situ OS models have corroborated the anti-tumor efficacy of Mg-ZIF nanozymes, while also validating their biosafety. The design of Mg-ZIF nanozymes opens a new avenue for the treatment of OS, offering a promising therapeutic strategy.